Stackelberg equilibrium in a mixed duopoly - Kalashnikov, Vyacheslav V.; Cordero Franco, Álvaro Eduardo; Kalashnikov, Vitaly (Institute of Electrical and Electronics Engineers, 2007)
We investigate Stackelberg mixed duopoly models where a state-owned public firm maximizing domestic social surplus, and a foreign firm compete. We examine a desirable role (either leader or follower) of both firms. Under these conditions, the firms may have two different types of optimal reaction at the Cournot equilibrium: weak or strong. We compare the profits and domestic social surplus and compare the volume of commodities for various combinations of weak and strong leaders and followers